2018
DOI: 10.1016/j.jcrs.2018.07.040
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of a new hydrophobic acrylic intraocular lens in the rabbit model

Abstract: The new IOL showed biocompatibility and stability comparable to the control IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The authors concluded that the Clareon is likely to perform as well as, and possibly better than, AcrySof in terms of Nd:YAG capsulotomy rates. Furthermore, an in vivo rabbit study in fifteen New Zealand white rabbits with a follow up of 1 month did not detect a difference in PCO and anterior capsule opacification, as observed during clinical and pathological evaluation between the Clareon and the AcrySof IOL [19]. Our human ex vivo data in the capsular bag model shows a comparable result.…”
Section: Discussionsupporting
confidence: 60%
“…The authors concluded that the Clareon is likely to perform as well as, and possibly better than, AcrySof in terms of Nd:YAG capsulotomy rates. Furthermore, an in vivo rabbit study in fifteen New Zealand white rabbits with a follow up of 1 month did not detect a difference in PCO and anterior capsule opacification, as observed during clinical and pathological evaluation between the Clareon and the AcrySof IOL [19]. Our human ex vivo data in the capsular bag model shows a comparable result.…”
Section: Discussionsupporting
confidence: 60%
“…12 The IOL is made of a hydrophilic (2-hydroxymethyl methacrylate) and a hydrophobic polymer component (phenylethyl acrylate), with an ultraviolet light-filtering and a blue light-filtering chromophore incorporated into the material. [13][14][15][16] The Clareon IOL has a water content of 1.5% at 35°C, a refractive index of 1.55, and a glass transition temperature of 9.1°C. [13][14][15][16] The IOL is preloaded in an automated preloaded delivery system (AutonoMe CNA0T0) and available in powers of +6.00 to +30.00 D.…”
Section: Intraocular Lensesmentioning
confidence: 99%
“…[13][14][15][16] The Clareon IOL has a water content of 1.5% at 35°C, a refractive index of 1.55, and a glass transition temperature of 9.1°C. [13][14][15][16] The IOL is preloaded in an automated preloaded delivery system (AutonoMe CNA0T0) and available in powers of +6.00 to +30.00 D.…”
Section: Intraocular Lensesmentioning
confidence: 99%
“…Both AcrySof® IQ and Clareon® lenses feature square edge designs that aim to prevent PCO by inhibiting epithelial cell migration. Studies that have compared the incidence of PCO following implantation of SN60WF and Clareon® IOLs in rabbit and explanted capsular bags from human cadavers reported no difference in PCO incidence or progression rates [13,14]. However, a large-scale meta-analysis reported that incidence of PCO requiring Nd: YAG capsulotomy within the first year of surgery in humans was higher in eyes that received SN60WF lenses compared to Clareon® lenses (1.44% versus 0.62%, respectively) [15].…”
Section: Discussionmentioning
confidence: 99%